Manganese-copper damping alloy powder based on SLM process and preparation method of manganese-copper damping alloy powder
Through vacuum induction VIGA preparation method and SLM heat treatment technology, the problem of uneven particle size distribution of manganese-copper damping alloy powder is solved, the uniform particle size and excellent mechanical properties of manganese-copper damping alloy powder are achieved, and the comprehensive mechanical properties of 3D printing standard parts are improved. and damping performance.
Patent Information
- Application Number
- CN202411542671.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing SLM process, the particle size distribution of manganese copper damping alloy powder is uneven, resulting in poor molding quality and the molded parts are prone to cracks, pores and high surface roughness.
The vacuum induction VIGA preparation method was used to prepare manganese copper damped alloy powder, and heat treatment was carried out through SLM technology, and process parameters such as speed, power and pass spacing were adjusted to obtain uniform particle size and excellent mechanical properties.
The particle size distribution of manganese-copper damping alloy powder is achieved, with high spherical shape and low cost, and the comprehensive mechanical properties and damping performance of 3D printed standard parts are improved, including room temperature tensile strength, yield strength and elongation improvement, as well as damping performance Optimization of Q-1.
Smart Images

Figure CN119457119A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to manganese-copper damping alloy powder based on SLM process and a preparation method thereof. Background Art
[0002] With the rapid development of additive manufacturing technology, selective laser melting (SLM), as a high-precision, high-performance 3D printing technology, has been widely used in aerospace, automotive industry, biomedicine and other fields. SLM technology uses high-energy laser beams to melt metal powder layer by layer according to computer-aided design (CAD) models to achieve one-time molding of complex structural parts, which not only improves material utilization, but also greatly shortens the product development cycle.
[0003] Manganese copper is an alloy material with excellent damping performance and good electrical conductivity. Its main components include copper, manganese, and a small amount of nickel, iron and other elements. Due to its excellent performance in vibration energy absorption, manganese copper alloy is widely used in the manufacture of shock absorbers, springs and other mechanical parts that require good damping properties. However, traditional casting or forging methods have many limitations in the production of manganese copper parts with complex shapes, such as high cost and difficult processing. In recent years, researchers have begun to explore the application of SLM technology in the molding of manganese copper damping alloy powder to overcome the limitations of traditional manufacturing methods. SLM technology can accurately control the molten pool size and cooling rate, which helps to form a fine and uniform microstructure, thereby improving the comprehensive mechanical properties of the material. In addition, by adjusting process parameters such as laser power and scanning speed, the sintering density and porosity of manganese copper alloy powder can be effectively regulated to further optimize the damping effect of the final product.
[0004] At present, in SLM molding, the traditional manganese-copper damping alloy powder is prone to the following technical problems:
[0005] 1. Uneven particle size distribution may lead to poor powder spreading and affect the molding quality. In addition, non-spherical or poorly fluid powders are prone to accumulation during the laying process, affecting the uniformity of laser melting and molding accuracy.
[0006] 2. During the molding process, cracks may appear inside or on the surface of the molded part due to the thermal stress generated during rapid heating and cooling; and during the laser melting process, if the gas is not discharged in time, pores will be formed inside the molded part, reducing the density and mechanical properties of the material; thermal stress concentration leads to deformation.
[0007] 3. The surface roughness of SLM molded parts is usually high, and additional post-processing such as polishing, heat treatment, etc. is required to achieve the required surface quality.
[0008] Therefore, it is necessary to prepare a manganese-copper damping alloy powder suitable for the SLM process, which has uniform particle size distribution, stable performance and low cost. Summary of the invention
[0009] In order to overcome the deficiencies of the prior art, the present invention provides a manganese-copper damping alloy powder for SLM process and a preparation method thereof, which can overcome the problems of uneven particle size distribution, unstable performance and high cost.
[0010] In order to achieve the above-mentioned purpose, the present invention provides a manganese-copper damping alloy powder based on the SLM process, the chemical composition of the powder is as follows by weight percentage: Cu ≥ 20%, Fe: 2-5.0%, Ni: 4.9-5.5%, Si: ≤ 0.15%, and the rest is Mn and unavoidable impurity elements; based on the above-mentioned proportion of components, after heat treatment by SLM technology, it is printed by 3D printing process, and the process is: speed 1000mm / s, power 250W, and pass spacing 0.15mm.
[0011] Preferably, the powder is prepared by vacuum induction VIGA preparation method to prepare the master alloy and printed by EOS290 metal printer.
[0012] Preferably, the VIGA method powder making process is: the master alloy rod is polished and ground and placed in an induction furnace for melting, the obtained molten metal is poured into a magnesium oxide tundish, flows through a nozzle and flushes the high-temperature liquid flow with high-purity argon gas for atomization powder making; the obtained metal powder is cooled and solidified and then stored in a powder collecting tank.
[0013] Preferably, the obtained metal powder is subjected to mechanical vibration and airflow classification and screening to obtain powders of different particle size ranges, and then vacuumed and stored.
[0014] Preferably, the powder ratio needs to be heat treated by SLM technology, and the heat treatment process is: temperature of 880°C, insulation time of 1h, water cooling temperature of 450°C, water cooling time of 4h, and air cooling to room temperature.
[0015] The present invention also provides a preparation method for preparing manganese-copper damping alloy powder based on SLM process, and the specific steps include:
[0016] S1: A master alloy is prepared by vacuum induction VIGA preparation method, wherein the composition of the master alloy is as follows by weight: Cu ≥ 20%, Fe: 2-5.0%, Ni: 4.9-5.5%, Si: ≤ 0.15%, and the rest is Mn and unavoidable impurity elements;
[0017] S2: The master alloy rod is polished and ground and then melted in an induction furnace. The obtained molten metal is poured into a magnesium oxide tundish, flows through a nozzle and flushes the high-temperature liquid flow with high-purity argon gas for atomization and powdering. The obtained metal powder is cooled and solidified and then stored in a powder collecting tank.
[0018] S3: Powders with different particle sizes are obtained through mechanical vibration and airflow classification and sieving, and then stored in vacuum;
[0019] S4: Put the manganese-copper damping alloy powder into the SLM laser additive manufacturing equipment to prepare mechanical properties standard parts;
[0020] S5: heat treatment is performed on the prepared standard parts. The heat treatment process is as follows: temperature is 880°C, holding time is 1h, water cooling temperature is 450°C, water cooling time is 4h, and air cooling is performed to room temperature.
[0021] The method for preparing manganese-copper damping alloy powder for SLM process provided by the present invention has the following beneficial effects:
[0022] 1. The manganese-copper damping alloy powder prepared by the VIGA method has a high fine powder recovery rate in the range of 15 to 53 μm, high loose density, good sphericity, and a smooth and complete surface, which meets the requirements of the 3D printing process for metal powder.
[0023] 2. According to the physical properties of the invented manganese-copper damping alloy powder, matching SLM laser printing process parameters are proposed, so that the final 3D printed standard parts have extremely excellent comprehensive mechanical properties and damping properties: room temperature tensile strength > 560MPa, yield strength > 300MPa, elongation exceeds 20%, and the damping performance Q-1 at room temperature reaches above 0.028. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Flow chart of the preparation method of manganese-copper damping alloy powder based on SLM process. DETAILED DESCRIPTION
[0025] Example 1
[0026] The invention provides a manganese-copper damping alloy powder for SLM process, wherein the chemical composition of the powder is as follows by weight: Cu: 22%, Fe: 4%, Ni: 5%, Si: 0.1%, and the rest is Mn and inevitable impurity elements; based on the above proportioning components, after heat treatment by SLM technology, 3D printing process is adopted for printing, and the process is as follows: speed 1000mm / s, power 250W, and pass spacing 0.15mm.
[0027] The functions of each element are as follows:
[0028] The Cu matrix element can significantly improve the damping performance and hot and cold processing performance of the manganese-copper alloy. The mechanism is that the copper undergoes a crystal structure transformation with temperature changes in the solid solution state, generating a large number of crystal interfaces, which absorb a lot of vibration energy during the interface movement process. Therefore, in this embodiment, the mass percentage of copper in the manganese-copper alloy is 22%.
[0029] The Fe element can serve as the embryonic nucleus of stress-induced martensite and promote the formation of a large amount of γ martensite in the alloy. At the same time, Fe can also promote the spinodal decomposition of the Mn alloy, produce Mn-poor or Mn-rich areas, promote the precipitation of grain boundaries, and improve the damping performance of the alloy. Therefore, the mass percentage of iron in the manganese-copper alloy is within 4%.
[0030] Nickel element: The manganese copper damping alloy has poor corrosion resistance due to its high manganese content. Therefore, by adding alloying elements such as nickel, the manganese content is reduced, the mechanical properties, casting process and corrosion resistance of the material are improved to meet the use requirements. The nickel mass percentage of the manganese copper alloy is preferably within 5%.
[0031] Si is a harmful element in manganese copper alloy, which will form oxide inclusions and have a great influence on mechanical properties. Therefore, the mass percentage of silicon in Ming manganese copper alloy is 0.1%.
[0032] The powder ratio needs to be heat treated by SLM technology. By providing a 3D printing process for printing manganese-copper damping alloy powder, the prepared manganese-copper damping alloy powder has controllable particle size, high sphericity, low manufacturing cost, high metal powder yield and is suitable for industrial production.
[0033] The powder is prepared by vacuum induction VIGA preparation method to prepare the master alloy and is printed by EOS290 metal printer.
[0034] Based on the manganese-copper damping alloy powder for SLM process provided by the present invention, the present invention also provides a preparation method, and the specific steps include:
[0035] A master alloy is prepared by a vacuum induction VIGA preparation method, wherein the composition of the master alloy is as follows by weight: Cu: 22%, Fe: 4%, Ni: 5%, Si: 0.1%, and the rest is Mn and unavoidable impurity elements;
[0036] The master alloy rod is polished and ground and then put into an induction furnace for melting. During melting, the master alloy is induction heated to 1450°C. After the master alloy is completely melted, the obtained molten metal is poured into a magnesium oxide tundish, flows through a nozzle and flushes the high-temperature liquid flow with high-purity argon gas for atomization and powdering; the obtained metal powder is cooled and solidified and then stored in a powder collecting tank;
[0037] Powders of different particle size ranges were obtained through mechanical vibration and airflow classification and sieving, and then stored in a vacuum chamber. The loose density of powders in different particle size ranges was detected by HYL-1001 multifunctional powder physical property tester, the fluidity of powders was measured by Hall flowmeter, and the particle size distribution of M2052 alloy powder was detected by Bettersize2000 laser particle size analyzer. The morphology of powder surface and internal solidification structure was observed by Zeiss40MAT optical microscope and FEIQuanta650FEG thermal field emission scanning electron microscope.
[0038] Put manganese-copper damping alloy powder into SLM laser additive manufacturing equipment to prepare mechanical performance standard parts;
[0039] Specifically, manganese-copper damping alloy powder with a particle size range of 15 to 53 μm is placed in an SLM laser additive manufacturing device to prepare standard parts with mechanical properties.
[0040] The prepared standard parts were heat treated, and the heat treatment process was as follows: temperature 880°C, holding time 1h, water cooling temperature 450°C, water cooling time 4h, and air cooling to room temperature; 3D printing technology was used for printing, and the process was as follows: speed 1000mm / s, power 250W, and pass spacing 0.15mm.
[0041] Example 2
[0042] The master alloy is prepared by vacuum induction VIGA preparation method, and the composition of the master alloy is as follows by weight: Cu: 23%, Fe: 2%, Ni: 5.5%, Si: 0.15%, and the rest is Mn and inevitable impurity elements;
[0043] The master alloy rod is polished and ground and then put into an induction furnace for melting. During melting, the master alloy is induction heated to 1500°C. After the master alloy is completely melted, the obtained molten metal is poured into a magnesium oxide tundish, flows through a nozzle and flushes the high-temperature liquid flow with high-purity argon gas for atomization and powdering; the obtained metal powder is cooled and solidified and then stored in a powder collecting tank;
[0044] Powders of different particle size ranges were obtained through mechanical vibration and airflow classification and sieving, and then stored in a vacuum chamber. The loose density of powders in different particle size ranges was detected by HYL-1001 multifunctional powder physical property tester, the fluidity of powders was measured by Hall flowmeter, and the particle size distribution of M2052 alloy powder was detected by Bettersize2000 laser particle size analyzer. The morphology of powder surface and internal solidification structure was observed by Zeiss40MAT optical microscope and FEIQuanta650FEG thermal field emission scanning electron microscope.
[0045] Put manganese-copper damping alloy powder into SLM laser additive manufacturing equipment to prepare mechanical performance standard parts;
[0046] Specifically, manganese-copper damping alloy powder with a particle size range of 15 to 53 μm is placed in an SLM laser additive manufacturing device to prepare standard parts with mechanical properties.
[0047] The prepared standard parts were heat treated, and the heat treatment process was: temperature 880℃, holding time 1h, water cooling temperature 450℃, water cooling time 4h, air cooling to room temperature. The 3D printing process was used for printing, and the process was: speed 1000mm / s, power 250W, and pass spacing 0.15mm; in actual operation, the printing process needs to be appropriately adjusted in combination with specific test conditions, and the specific printing situation should be observed in real time.
[0048] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. Manganese-copper damping alloy powder for SLM process, characterized in that: The chemical composition of the powder is as follows by weight: Cu ≥ 20%, Fe: 2-5.0%, Ni: 4.9-5.5%, Si: ≤ 0.15%, and the rest is Mn and inevitable impurity elements; based on the above-mentioned proportions, after heat treatment with SLM technology, it is printed using a 3D printing process, and the process is: speed 1000 mm / s, power 250 W, and pass spacing 0.15 mm.
2. The manganese-copper damping alloy powder for SLM process according to claim 1, characterized in that: The powder was prepared into master alloy using vacuum induction VIGA preparation method and printed using EOS290 metal printer.
3. The manganese-copper damping alloy powder for SLM process according to claim 2, characterized in that: The VIGA method powder making process is as follows: the master alloy rod is polished and ground and then melted in an induction furnace, the obtained molten metal is poured into a magnesium oxide tundish, flows through a nozzle and flushes the high-temperature liquid flow with high-purity argon gas to perform atomization powder making; the obtained metal powder is cooled and solidified and then stored in a powder collecting tank.
4. The manganese-copper damping alloy powder for SLM process according to claim 3, characterized in that: The obtained metal powder is subjected to mechanical vibration and airflow classification and screening to obtain powders with different particle size ranges, and then vacuumed and stored.
5. The manganese-copper damping alloy powder for SLM process according to claim 1, characterized in that: The powder ratio needs to be heat treated by SLM technology. The heat treatment process is: temperature 880℃, insulation time 1h, water cooling temperature 450℃, water cooling time 4h, and air cooling to room temperature.
6. A preparation method for preparing the manganese-copper damping alloy powder for SLM process according to claim 1, characterized in that: The specific steps include: S1: A master alloy is prepared by a vacuum induction VIGA preparation method, wherein the composition of the master alloy is as follows by weight: Cu ≥ 20%, Fe: 2-5.0%, Ni: 4.9-5.5%, Si: ≤ 0.15%, and the rest is Mn and unavoidable impurity elements; S2: The master alloy rod is polished and ground and then melted in an induction furnace. The obtained molten metal is poured into a magnesium oxide tundish, flows through a nozzle and flushes the high-temperature liquid flow with high-purity argon gas for atomization and powdering. The obtained metal powder is cooled and solidified and then stored in a powder collecting tank. S3: Powders with different particle sizes are obtained through mechanical vibration and airflow classification and sieving, and then stored in vacuum; S4: Put the manganese-copper damping alloy powder into the SLM laser additive manufacturing equipment to prepare mechanical properties standard parts; S5: heat treatment is performed on the prepared standard parts. The heat treatment process is as follows: temperature is 880°C, holding time is 1h, water cooling temperature is 450°C, water cooling time is 4h, and air cooling is performed to room temperature.